Altered Patterns of Compositional and Functional Disruption of the Gut Microbiota in Typhoid Fever and Nontyphoidal Febrile Illness. (26th June 2020) - Haak, Bastiaan W; de Jong, Hanna K; Kostidis, Sarantos; Giera, Martin; Maude, Rapeephan R; Samad, Rasheda; Wijedoru, Lalith; Ghose, Aniruddha; Faiz, Mohammed Abul; Parry, Christopher M; Wiersinga, W Joost
Abstract: Background: Experimental murine models and human challenge studies of Salmonella Typhi infection have suggested that the gut microbiome plays an important protective role against the development of typhoid fever. Anaerobic bacterial communities have been hypothesized to mediate colonization resistance against Salmonella species by producing short-chain fatty acids, yet the composition and function of the intestinal microbiota in human patients with typhoid fever remain ill defined. Methods: We prospectively collected fecal samples from 60 febrile patients admitted to Chittagong Medical College Hospital, Bangladesh, with typhoid fever or nontyphoidal febrile illness and from 36 healthy age-matched controls. The collected fecal samples were subjected to 16s rRNA sequencing followed by targeted metabolomics analysis. Results: Patients with typhoid fever displayed compositional and functional disruption of the gut microbiota compared with patients with nontyphoidal febrile illness and healthy controls. Specifically, typhoid fever patients had lower microbiota richness and alpha diversity and a higher prevalence of potentially pathogenic bacterial taxa. In addition, a lower abundance of short-chain fatty acid–producing taxa was seen in typhoid fever patients. The differences between typhoid fever and nontyphoidal febrile illness could not be explained by a loss of colonization resistance after antibiotic treatment, as antibiotic exposure in both groups was similar. Conclusions: his first report on the composition and function of the gut microbiota in patients with typhoid fever suggests that the restoration of these intestinal commensal microorganisms could be targeted using adjunctive, preventive, or therapeutic strategies.